The new forms of organization of the exit medical help to the inhabitants of boreal districts of Siberia - T. V. Solomatina; L. V. Kapilevich (Бюллетень сибирской медицины, 2002)
Alongside with economic problems of development of North the important place is borrowed by a problem of guarding of health of the population. The population of Boreal districts of Siberia is subject to effect of a lot of the unfavorable factors both connatural (climatic conditions), and anthropogenic (ecological trouble) character. A corollary it is the high level of a case rate, violation on the part of cardiovascular, nervous and other systems of an organism. The inhabitants of boreal districts, workers of oil-extracting branch are bunch of the boosted risk on creation of a pathology of organs of a circulation and endocrine system. The data quota needs a regular control of a state of health and opportune rendering of a medical care in amplate volume. The optimal form of organization of a medical care to the population of Boreal districts is the direction of exit medical crews in items of their residing. Such form of work is economically favourable and at the least expenditures allows to reach appreciable social and medico-sanitary effect.